2012
DOI: 10.1074/jbc.m112.351809
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of Escherichia coli Diaminopropionate Ammonia-lyase Reveals Mechanism of Enzyme Activation and Catalysis

Abstract: Background: DAPAL is a novel PLP-dependent enzyme involved in the degradation of DAP, a nonstandard amino acid. Results: Striking structural differences were observed between apo-and holo-EcDAPAL, and structure with a PLP-aminoacrylate intermediate bound at the active site was obtained. Conclusion: Enzyme undergoes apo to holo structural transitions and follows a two-base mechanism of catalysis. Significance: The results provide insights into the catalytic mechanism of DAPAL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 49 publications
3
16
0
Order By: Relevance
“…IlvA is not the only enzyme whose mechanism could produce free 2AA in vivo . Organisms have other PLP enzymes whose reaction mechanisms may involve 2AA derived from serine, cysteine, tryptophan, or other metabolites (4347). PLP-dependent enzymes are ubiquitous, and the need for this cofactor is a selective pressure for the evolution of RidA enzymes to avert damage caused by enamine/imine intermediates.…”
Section: Discussionmentioning
confidence: 99%
“…IlvA is not the only enzyme whose mechanism could produce free 2AA in vivo . Organisms have other PLP enzymes whose reaction mechanisms may involve 2AA derived from serine, cysteine, tryptophan, or other metabolites (4347). PLP-dependent enzymes are ubiquitous, and the need for this cofactor is a selective pressure for the evolution of RidA enzymes to avert damage caused by enamine/imine intermediates.…”
Section: Discussionmentioning
confidence: 99%
“…Among the residues at the active site that showed a change of orientation between eDAPAL and eDAPAL‐DAP complex were Asp120 and Asp189. It was shown previously that D120N and D189N eDAPAL exhibited reduced activity with l ‐ and d ‐DAP . The corresponding residues in sDAPAL are Asp125 and Asp194.…”
Section: Resultsmentioning
confidence: 77%
“…D125E sDAPAL, however, did not exhibit any detectable activity with d ‐DAP, although significant activity was observed with l ‐DAP (Table ). These results suggested that Asp125 might be essential for proton abstraction from d ‐DAP but not l ‐DAP, as observed for eDAPAL . Spectral studies were carried out with both isomers of DAP for D125E sDAPAL and compared with those of sDAPAL as a control.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…4C). Such an environment around the nitrogen atom of the pyridine ring would not favor its electron withdrawing potential necessary for its co-factor function (32). It is likely that a similar situation is found in the C. albicans THI5p homolog structure (12).…”
Section: Table 2 Quantification Of Iron By the Ferrozine Assaymentioning
confidence: 95%